Re: Forceps-related endoscopic transpapillary biliary biopsy programmes, reply: endoscopic biopsy techniques for proximal biliary strictures - Wenbo Meng,; Ping Yue,; Zhiwen Luo,; Xun Li, (Turkish Journal of Gastroenterology, 2019)
-